Ouabain inhibition of Na/K-ATPase across the retina prevents signed refractive compensation to lens-induced defocus, but not default ocular growth in young chicks - Murphy, Melanie J (F1000Res, 2013)
Purpose: The relevance of retinal integrity and energy pathways to ocular growth and induction of refractive errors has seldom been investigated. Thus, we used ouabain to target the channels that are essential for the maintenance of membrane potentials in cells, sodium potassium ATPase (Na/K-ATPase), to examine refractive compensation and ocular growth in response to lens-induced defocus in the chick. Methods:  A single intravitreal injection of 1 mM ouabain in dimethyl sulfoxide (DMSO) carrier or DMSO alone was followed by monocular defocus with positive or negative 10 D lens (or no lens) from post-hatching days 5-9 under 12/12 hr light/dark conditions. Biometry and dark-adapted flash and electroretinography (ERG) were conducted on day 9, followed by immunohistological analyses. Results: Ouabain inhibited differential ocular growth and refractive compensation to signed defocus compared to DMSO. By 4-days post-ouabain injection all components of the typical ERG responses to light had been eliminated, and widespread histological damage was apparent, though some ‘default state’ ocular growth was measurable. Immunohistochemistry demonstrated reduction in the specialized water channel Aquaporin 4 (AQP4) expression and increased evidence of caspase 3 expression (a cell death associated protein) in ouabain-treated eyes compared with DMSO alone. Conclusion: The current study demonstrates that blockade of photoreceptor and inner retinal responses to light onset and offset by ouabain inhibits differential refractive compensation to optical blur, but does not prevent ocular growth.